Judicial Independence: Political Influence in Modern Democracies - Vannai Chea; Sok Kuon (International Journal of Law and Political Authority, 2026)
Judicial independence constitutes a core element of democratic constitutionalism, yet its resilience is increasingly challenged by political influence in modern democracies. This article examines how political actors shape judicial autonomy through institutional mechanisms that formally comply with constitutional frameworks while substantively constraining judicial discretion. Using a qualitative doctrinal and comparative approach, the study integrates theoretical scholarship, cross-national empirical findings, and institutional analysis to explore the relationship between judicial independence and democratic governance. The findings demonstrate that judicial independence is best understood as a dynamic equilibrium between legal authority and political power, rather than as a fixed constitutional attribute. Institutional arrangements governing appointments, judicial councils, budgets, and jurisdiction emerge as central mediators of political influence. The erosion of judicial independence is shown to undermine democratic accountability, public trust, and the protection of rights, contributing to broader patterns of democratic backsliding. The study concludes that safeguarding judicial independence is essential for sustaining democratic legitimacy and preventing the concentration of unchecked political power.